IDENTIFICATION OF LOCATION-BASED DIFFERENTIAL ITEM FUNCTIONING OF 2022/2023 GENERAL STUDIES EXAMINATION (GSE) OF SA’ADATU RIMI COLLEGE OF EDUCATION KUMBOTSO, KANO, NIGERIA - ABDULLAHI , ABUBAKAR; LAWAN, AMINA ABDUKADIR; KAMAR, KHALIL YAHYA (Sokoto Educational Review, 2025)
This study explored location-based Differential Item Functioning (DIF) in the General Studies Examination (GSE) Mathematics test administered to NCE I students at Sa’adatu Rimi College of Education, Kumbotso, Kano State, Nigeria. Employing an ex post facto design, the research examined a population of 6,132 NCE I students, from which a sample of 500 students was selected using a multi-stage sampling technique. Data from the 2022/2023 GSE 122 Examination, consisting of 30 items, were analyzed through binary logistic regression and Item Response Theory (IRT)-based item bias analysis. The findings revealed that 20.0% of the test items exhibited magnitude-level DIF, significantly favoring rural students over their urban counterparts, indicating that the examination items were not entirely fair across locations. The study concludes that location-based DIF exists in the GSE examination and recommends further investigation into variables such as location, gender, school type, tribe, culture, socio-economic status, and marital status to identify potential sources of DIF in the GSE 122 examination at Sa’adatu Rimi College of Education, Kumbotso.